Carbon nanotube functionalizations and the development of carbon nanotube-enzyme hybrid catalyst for the degradation of 3,4-dihydroxybenzoic acid pollutant in water / Rasel Das - Das, Rasel (2015)
The efficient handling of both the persisting and newly emerging pollutants is a must, since they are continuously defiling the limited fresh water resources, seriously affecting the terrestrial, aquatic, and aerial flora and fauna. The 3,4-Dihydroxybenzoic Acid (3,4-DHBA) is a major phenol-type toxic water pollutant having detrimental effects on animal and human health. It causes oxidative stress, neurotoxicity, hepatotoxicity and skin cancer when ingested at high levels by animals (≥ 1.0 μmole) and humans (≥ 5.0 mM). Currently, 3,4-DHBA is handled by a few methods such as adsorption, chemical oxidation and microbial decontaminations which are non-specific, insensitive, time consuming, costly and generating chemical masses to the environment. Recently, immobilized enzymes onto nanomaterial supports have been evolved a new generation of Nanobiohybrid catalysts which have versatile applications in waste water purifications. Protocatechuate 3,4-dioxygenase (3,4-POD) has long been used for the degradation of 3,4-DHBA. However, immobilizing 3,4-POD onto nanomaterial for enhancing its stabilities, reusability and reduced cost has remained unexplored. Here we filled up this gap by developing a novel Nanobiohybrid catalyst through covalent immobilization of 3,4-POD onto multi-walled carbon nanotube (MWCNT) surfaces. MWCNTs were selected since they are low-cost materials with large surface area, high aspect ratio, greater chemical reactivity, and less chemical mass and adverse environmental impact. Unfortunately, pristine MWCNTs are hydrophobic and often contaminated with various impurities such as amorphous carbons, metals and ashes which hinder its conjugation with biomolecules. Here we attempted to develop simple methods for MWCNT purification and functionalization with bio-conjugating functionalities with added water dispersion properties. We observed that HCl/H2O2 treatment annihilated more amorphous carbons and metals from the MWCNTs compared with HCl alone and KOH/H2O2 methods. On the other hand, H2SO4/HNO3 functionalized MWCNTs (F-MWCNTs) were more soluble in water because of their higher number of -COOH functionalities than those of HNO3/H2O2 and KMnO4 functionalizations. Thus HCl/H2O2 purified and H2SO4/HNO3 F-MWCNT was used as support matrix for 3,4-POD immobilization. Convincing results from scanning electron microscopy, transmission electron microscopy, atomic force microscopy, attenuated total reflectance infrared and ultraviolet-visible spectroscopy studies confirmed that the 3,4-POD was successfully immobilized onto F-MWCNT surfaces, and maximum loading was found 1060 μg of 3,4-POD/mg of F-MWCNTs. Circular dichroism spectra showed that the Nanobiohybrid could experience with 44% of structural changes to its free 3,4-POD conformations that was capable to retain 93% of relative activity and about 50% of catalytic efficiency to its free 3,4-POD. In addition, Nanobiohybrid demonstrated higher alkaline and thermo stabilities as compared with free 3,4-POD. Nanobiohybrid retained 56% of residual activity which was 41 and 39% for the free 3,4-POD at 4 and 25oC on 30 days storage, respectively. Besides, the Nanobiohybrid exhibited >60% of residual activity even after ten cycle of operations, suggesting that it could defray the production costs of free 3,4-POD for long term uses in waste water purifications. Finally, the Nanobiohybrid removed 71% of 3,4-DHBA from water in less than four hour, paving its application for the efficient removal of toxic water pollutants with reduced costs and time.